Abundance of East coast Australian humpback whales (Megaptera novaeangliae) in 2005 estimated using multi-point sampling and capture-recapture analysis - Paton, David A.; Brooks, Lyndon; Burns, Daniel; Franklin, Trish; Franklin, Wally; Harrison, Peter; Baverstock, Peter (J. Cetacean Res. Manage., 2020)
The humpback whales (Megaptera novaeangliae) that migrate along the east coast of Australia were hunted to near extinction during the last century. This remnant population is part of Breeding Stock E. Previous abundance estimates for the east Australian portion of Breeding Stock E have been based mainly on land-based counts. Here we present a capture-recapture abundance estimate for this population using photo-identification data. These data were collected at three locations on the migration route (Byron Bay – northern migration, Hervey Bay and Ballina – southern migration) in order to estimate the population of humpback whales that migrated along the east coast of Australia in 2005. The capture-recapture data were analysed using a variety of closed population models with a model-averaged estimate of 7,041 (95% CI 4,075–10,008) whales.